Inguinodynia in patients submitted to conventional inguinal hernioplasty - BRUNO GARCIA DIAS; MARCELO PROTÁSIO DOS SANTOS; ANA BARBARA DE JESUS CHAVES; MARIANA WILLIS; MARCIO COUTO GOMES; FERNANDES TAVARES ANDRADE; VALDINALDO ARAGÃO DE MELO; PAULO VICENTE DOS SANTOS FILHO (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Objective : to evaluate the incidence of chronic pain and its impact on the quality of life of patients submitted to inguinal hernioplasty using the Lichtenstein technique. Methods : this was a descriptive, cross-sectional study of patients operated under spinal anesthesia from February 2013 to February 2015 and who had already completed six postoperative months. We questioned patients about the presence of chronic inguinal pain and, if confirmed, invited them to a consultation in which we assessed the pain and its impact on quality of life. Results : out of 158 patients submitted to the procedure, we identified 7.6% as having inguinodynia. Of these, there was an impact on the quality of life in 25%. Conclusion : the incidence of inguinodynia after hernioplasty with repercussion in quality of life was similar to the one of found in the world literature.